Exploring the bidirectional relationship between childhood BMI z-scores and harsh parenting measures: a longitudinal study - Chew, Jacinth (Nanyang Technological University, 2024)
The rising prevalence of childhood obesity worldwide makes it increasingly important to understand its mechanisms, particularly those related to aspects of the family environment such as parenting practices. In Singapore, the persistence of harsh parenting as a normative practice offers a unique opportunity to investigate its connection to obesity, in a culture influenced by both Eastern and Western values. This study investigates the relationship between harsh parenting practices of physical coercion and verbal hostility, and childhood BMI z-scores, measured through BMI z-scores. Longitudinal data from 402 mother-child dyads was obtained from a subset of the Growing Up in Singapore Towards healthy Outcomes (GUSTO) cohort. Harsh parenting practices were measured using the Physical Coercion and verbal Hostility subscales from the Parenting Styles and Dimensions Questionnaire – Short Version at three timepoints (4.5, 8.5, and 10.5 years of age), while BMI z-scores were calculated at 4.5, 8 and 10 years of age. Linear mixed models did not find significant associations between physical coercion or verbal hostility and BMI z-scores in either direction, but an interaction effect suggested that BMI z-scores at year 4.5 could predict greater increases in verbal hostility from year 4.5 to year 8.5. There were also some observable trends suggesting potential ethnic variations in usage patterns of physical coercion and verbal hostility across the developmental trajectory. Future research should expand to include paternal data, and other dimensions of parenting behaviours specific to authoritative, permissive, and negligent parenting styles.